CRISPR-Cas9 GENOME-EDITING TECHNOLOGY:A TRANSFORMATIVE TOOL FOR CURING HUMAN DISORDERS (Journal of Medical & Health Sciences Review, 2025)
CRISPR stands for “Clustered Regularly Interspaced Short Palindromic Repeats”, which form the foundation of an ancient immune system in single-cell organisms, especially bacteria and archaea. It has shown a positive therapeutic potential by modifying the genetic mutations responsible for incurable genetic disorders. CRISPR has several benefits over other gene-editing tools, as it is convenient, inexpensive and efficient. Despite therapeutic potential, CRISPR can also help to make animal models to study disease development and progression, and also to study the effect of new drugs. CRISPR can help to treat several genetic diseases, including cancers, allergic diseases, immunological disorders, cardiovascular diseases, viral infections, cystic fibrosis, muscular dystrophy, Huntington’s disease, metabolic disorders, blood disorders and eye-related disorders. CRISPR can also help to treat celiac disease by modifying the gliadin content in the wheat crop. Pharmaceutical and therapeutic companies are developing CRISPR therapies against genetic diseases and are concerned about the off- target effects of CRISPR, along with its ethical, legal and safety concerns. CRISPR laws are more stringent in the European Union than in the United States, which critics believe could hamper the investment in this research. The future holds great promise for CRISPR in treating diseases, developing medicines and fostering agricultural production.